The Effect of Employee Competency Development, Performance Evaluation, and Remuneration on Employee Performance Case Study of Religious Affairs Offices (KUA) in West Jakarta - Ade Rahmat Ridwan; Agus Suradika; Hasanah Hasanah; Resky Nuralisa Gunawan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study examines the effect of employee competency development, performance evaluation, and remuneration on employee performance at the Religious Affairs Offices (KUA) in West Jakarta. As a public institution responsible for delivering administrative and community religious services, KUA faces challenges in ensuring effective human resource performance amid bureaucratic constraints and limited performance-based incentives. The study aims to analyze how the three human resource management (HRM) dimensions competency development, evaluation, and remuneration affect overall employee performance. A quantitative explanatory research design was employed using a structured questionnaire distributed to 120 employees across eight KUA offices. Data were analyzed using multiple linear regression supported by descriptive and classical assumption tests. The results indicate that performance evaluation and remuneration have significant positive effects on employee performance, while competency development shows a positive but statistically insignificant effect. The model explains 49% of the variation in employee performance, suggesting that transparent evaluation systems and performance-based remuneration play a greater role than training programs alone in improving public service effectiveness. The findings contribute to strategic HRM theory by confirming that evaluation and reward mechanisms strengthen the link between competency and performance. It is concluded that integrating developmental, evaluative, and compensatory functions within a unified HR framework can enhance productivity and accountability in Indonesia’s public sector institutions.